Nucleotídeos e ácido glutâmico em dietas de leitões desmamados - Santos, Luan Sousa dos [UNESP] (2015)
The objectives of this research were to evaluate the effects of nucleotides (NU) and glutamic acid (AG) in the diet of pigs on performance and plasma lipid profile (total cholesterol - CT, triglycerides - TRI, HDL cholesterol and LDL + VLDL cholesterol ) (experiment I) and turnover of 13C in duodenal and jejunum mucosa (13C half-life) (experiment II). In both experiments we used experimental design of randomized blocks, with 2x2 factorial treatments, with two levels of NU (0 and 0.1%) and two levels of AG (0 and 1%), each treatament had seven replicated and three pigs per pen. The first experiment lasted 35 days and were used 84 piglets weaned at 21 days of age and average initial weight of 6.54 ± 0,70kg. In the second experiment, on days 3, 6, 9, 14, 21, 34 and 49 after weaning, were slaughtered three pigs per treatment and the day of weaning (day zero) were slaughtered three piglets, totaling 87 animals with initial weight 6.28 ± 0,13kg. There was no interaction of factors in the analyzed variables and not effects of NU and AG in daily feed intake, daily weight gain, CT, HDL cholesterol, TRI, LDL + VLDL cholesterol and 13C turnover in the intestinal mucosa. The use of NU in the diet has worsened (p≤0.05) feed conversion in the period 0-27 days, but this variable was not affected in the total period (0-35 days). We observed a decrease (P<0.0001) in plasma concentration of all variables after 56 days compared to 21 days of age and in the jejunal mucosa the 13C half-life was higher in lighter piglets (p≤0.05). It can be concluded therefore that the addition of AG and NU in the diets did not affect performance, the plasma lipid profile and 13C turnover in the duodenum and jejunum mucosa of weaned piglets in total nursery period